2022
DOI: 10.18502/jthc.v17i2.9842
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of a Type IV Dual Left Anterior Descending Artery and Ectopic Left Anterior Descending and Circumflex Arteries Requiring Surgery

Abstract: Congenital anomalous coronary arteries (CACAs) comprise an important variant of the coronary vasculature. They are benign in the vast majority of cases, whereas a small minority may be affected by serious consequences such as myocardial infarction, arrhythmia, cardiac arrest, and even death. We herein describe a 62-year-old man with sudden and severe substernal chest pain; Q waves in electrocardiographic leads II, III, and aVF; and positive serum troponin I enzyme. Left heart cardiac catheterization revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Understanding the different dual LAD types is crucial to the revascularization of the correct arterial system and the prevention of inappropriate arteriotomy. 17 The anterior LV wall and the septum may receive their blood supply from the 2 separate arteries; therefore, grafts to both vessels may be required if both the short and long LADs are significantly stenosed. 12 , 16 Furthermore, different anatomic characteristics at regular coronary angiography might be mistaken for mid-LAD occlusion since the extra artery cannot be seen, especially when the long LAD originates from the right coronary cusp.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the different dual LAD types is crucial to the revascularization of the correct arterial system and the prevention of inappropriate arteriotomy. 17 The anterior LV wall and the septum may receive their blood supply from the 2 separate arteries; therefore, grafts to both vessels may be required if both the short and long LADs are significantly stenosed. 12 , 16 Furthermore, different anatomic characteristics at regular coronary angiography might be mistaken for mid-LAD occlusion since the extra artery cannot be seen, especially when the long LAD originates from the right coronary cusp.…”
Section: Discussionmentioning
confidence: 99%
“…In various coronary angiographic studies, the reported incidence of dual LAD is 0.64-1.3%. 1,2 Accurate localization of coronaries in CABG surgery is imperative for identification and revascularization of the coronary arteries.…”
Section: Introductionmentioning
confidence: 99%